The ship of legality: the effects in central Italy’s schools (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
This article aims to analyse the effects of the experience of the “Nave della legalità” on school mobilisation in the regions of Central Italy. In particular, in the first part it will trace the value of this initiative through the stories of the teachers and schools that were most active and committed to education on legality; and in the second one it will emphasis on the legacy that the “Nave della legalità” has produced on the students who took part in the journey.
Keywords: mobilisation; school; legality; anti-mafia movement; mafias